THE DRAMATIC DOMINANT OF VASYL STEFANYK’S NOVELLAS - Lutsak, Svitlana; Vivcharyk, Nataliia (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The aim of the research is to analyze the genre features of Vasyl Stefanyk’s short stories, and first of all the dramatic component of their artistic structure. The main focus is on the short stories that formed the basis of the staging of the Zagrava Theater. Director Volodymyr Blavatsky chose the productions of the short story, the dynamic structure of the genre, which are revealed by modern researchers as dramas in the novel – «She is the Earth», «Sons», «Maria», «Thief», «Pious», «Morituri», and «My Word» (as a prologue). These works paid attention to the director, especially thematically expanded the scope of contemporary drama. The main article was the method of genealogical studies, combined with the methods of poetic analysis of the dominants of the internal organization of short stories by Vasyl Stefanyk. As a result of the research it was proved that it was the sharp conflict, dialogic speech, tension of the plot, temporal condensation, related issues, minimized descriptions that allowed the director to combine these works in one theatrical production. In addition, literary-critical reviews and works of Mykola Yevshan, Mykola Zerov, Mykhailo Rudnytsky, Ivan Franko, Lesia Ukrainka, etc. were used to characterize the ideological and artistic features of Vasyl Stefanyk’s short stories, which indicated the expressiveness of writing and minimal authorial presence in Vasyl Stefanyk’s short stories. The writer’s memoirs, archival materials, and diaspora research were also used, including Hryhor Luzhnytsky’s article «Son of the Earth», which outlined the specifics of the development of contemporary Ukrainian theater and the urgent need to enrich the repertoire with stagings by Ukrainian authors, including Vasyl Stefanyk. The main focus of the article is on the analysis of the short story «She is the Earth», which is central in the production of the same name. It is illustrated that the earth in the works and stagings of Vasyl Stefanyk appears in various guises – Motherland, home, people, family, symbolizes the inseparability of generations. The novelty of the article is the analysis of the longevity of the Ukrainian theatrical tradition, which was intuitively felt by the novelist Vasyl Stefanyk, transforming into an artistic structure of prose text, which led to the emergence of the original genealogical form of drama in the novel. This artistic tradition has found its refraction in the modern production of the Ivano-Frankivsk National Academic Drama Theater Ivan Franko’s drama-oratorio «She is the Earth».